Conductivity and Pseudocapacitance Optimization of Bimetallic Antimony–Indium Sulfide Anodes for Sodium‐Ion Batteries with Favorable Kinetics. Issue 10 (26th July 2018) - Huang, Yongxin; Wang, Ziheng; Jiang, Ying; Li, Shuaijie; Wang, Min; Ye, Yusheng; Wu, Feng; Xie, Man; Li, Li; Chen, Renjie
Abstract: Metal sulfides show promise for use in alkali‐ion batteries because of their high theoretical capacities. However, their poor cycling stability and rate performance hinder their further development. To avoid these issues, In2 S3 into Sb2 S3 is introduced to improve its electrochemical properties by optimizing its crystal structure and sodium storage mechanism. A heterostructure composed of In2 S3 and Sb2 S3 shows a unique morphology of formicary microspheres, which provide abundant channels for fast transfer of sodium ions, large surface area for a high pseudocapacitance effect, and enough voids to relieve volume expansion. A sodium‐ion battery containing the bimetallic sulfide anode exhibits a high reversible capacity of 400 mA h g −1 and long cycle life of about 1000 cycles. Similarly, a high capacity of ≈610 mA h g −1 is achieved for a lithium‐ion battery containing the anode. During sodiation/desodiation, the synergistic effect of In2 S3 and Sb2 S3 enhances electronic conductivity and supports the host structure, preventing collapse. The cycling performance and rate performance of the In2 S3 –Sb2 S3 anode are further improved by wrapping the electrode with carbon nanotubes. Even at a high current density of 3.2 A g −1, this carbon composite structure still shows a capacity of about 355 mA h g −1 . Abstract : A In2 S3 –Sb2 S3 heterostructure exhibits superior performance as a sodium‐ion batteries anode. This can be attributed to special construction providing strong pseudocapacitance effect and fast sodium storage dynamics; electrochemically inert In‐containing component forming a buffer layer to relieve volume expansion; and enhanced electronic conductivity of In2 S3 ‐Sb2 S3 and a reduced energy barrier for Na + ion migration.